Detecção de cantos em formas binárias planares e aplicação em recuperação de formas - Paula Júnior, Iális Cavalcante de (2013)
Content-based image retrieval (CBIR) applied to large scale datasets is a relevant and challenging problem present in medicine, biology, computer science, general cataloging etc. Image indexing can be done using visual information such as colors, textures and shapes (the visual translation of objects in a scene). Automated tasks in industrial inspection, trademark registration, biostatistics and image description use shape attributes, e.g. corners, to generate descriptors for representation, analysis and recognition; allowing those descriptors to be used in image retrieval systems. This thesis explores the problem of extracting information from binary planar shapes from corners, by proposing a multiscale corner detector and its use in a CBIR system. The proposed corner detection method combines an angulation function of the shape contour, its non-decimated decomposition using the Mexican hat wavelet and the spatial correlation among scales of the decomposed angulation signal. Using the information provided by our corner detection algorithm, we made experiments with the proposed CBIR. Local and global information extracted from the corners detected on shapes was used in a Dynamic Space Warping technique in order to analyze the similarity among shapes of different sizes. We also devised a strategy for searching and refining the multiscale parameters of the corner detector by maximizing an objective function. For performance evaluation of the proposed methodology and other techniques, we employed the Precision and Recall measures. These measures proved the good performance of our method in detecting true corners on shapes from a public image dataset with ground truth information. To assess the image retrieval experiments, we used the Bull’s eye score in three public databases. Our experiments showed our method performed well when compared to the existing approaches in the literature.